Prevalence and risk factors for hospital-acquired pneumonia after on-pump cardiac surgery - T. P. Kalashnikova; Yu. K. Podoksenov; N. O. Kamenshchikov; Yu. A. Arsenyeva; M. B. Gorchakova; I. V. Kravchenko; M. S. Kozulin; E. T. Romanyuk; S. A. Kunitsin; B. N. Kozlov; A. A. Boshchenko (Российский кардиологический журнал)
Aim. To study the prevalence and risk factors (RF) for hospital-acquired pneumonia (HAP) after on-pump cardiac surgery in a modern cohort of patients.Material and methods. This retrospective analysis of the medical records of cardiovascular surgery patients, operated on in the period from January 1, 2022 to December 31, 2022. The study consistently included 417 patients who underwent on-pump cardiac surgery. The incidence and timing of HAP development were assessed. The influence of the main demographic, clinical, and perioperative factors on HAP risk was studied.Results. The pneumonia prevalence per year was 27,6%, including after the Frozen Elephant Trunk (FET) procedure — 32%, after coronary artery bypass grafting (CABG) — 29,5%, after combined CABG and heart valve surgery — 26,2%, after isolated valve surgery — 25,9%, after thoracic aortic hemiarch replacement — 19,5%. Pneumonia developed on the 4,6±2,9 day after surgery. The risk of pneumonia increased with atrial fibrillation (AF) before surgery (odds ratio (OR) 3,17; 95% confidence interval (CI): 1,67; 6,02, p=0,0002), on-pump duration (OR 1,01; 95% CI: 1,00; 1,01; p=0,0006), aortic cross-clamping (OR 1,01; 95% CI: 1,00; 1,01; p=0,0002) and mechanical ventilation (OR 1,03; 95% CI: 1,01; 1,05; p=0,005). Pneumonia predictors were on-pump duration ≥96 min (sensitivity 67,7%, specificity 64,6%, AUC=0,681, p=0,0006) and mechanical ventilation ≥14 h (sensitivity 63,1%, specificity 69,3%, AUC=0,641, p=0,005), as well as preoperative AF (sensitivity 61%, specificity 75%, p=0,0002).Conclusion. Preoperative AF, on-pump duration ≥96 min and mechanical ventilation ≥14 h serve as categorical and quantitative predictors of postoperative HAP in a modern cohort of patients.